Allium Sativum, Hylocereus Polyrhizus And Its Combination Effectiveness On Lipid Profiles And Number Of Foam Cells In Rats With Dyslipidemia - Aisah, Wipi Sari; Sumarawati, Titiek; Nasihun, Taufiqurrachman (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2019)
Introduction: garlic extract (Allium sativum) and red dragon fruit extract (Hylocereus polyrhizus) have been used to improve lipid profile. Objective: to determine the effectiveness between garlic, red dragon extracts, and its combination on lipid profile and number of foam cells.Methods: experimental study with a pre-test post-test control group design. Twenty five Wistar rats were divided into 5 groups: Group (Sim-G); Group II (BP-84), Group III (BN-84), Group IV (B P-BN), Group V (negative Control /Neg-G). All rats were fed a high cholesterol diet to induce dyslipidemia. On day 28, blood samples were taken for lipid profile evaluation. After termination, aortic blood vessels were subjected to foam cell evaluation.Results: Post hoc test showed a significant decrease in total cholesterol, LDLc, Triglyceride and increase in HDLc in the treated groups compared to the negative control group (p<0.05. Mann Whitney test showed a significant differences in the number of foam cell in Sim-G, Gar-84, RD-84, dan Gar-RD compared to the Neg-G. There was a significant reduction in TC, LDLc, TG, and increase in HDLc in RD-84 compared to Gar-84 and Gar-RD. Foam cells number in Gar-RD insignificantly differ from Sim-G, p>0.05.Conclusion: Red dragon fruit extract was more effective to lower lipid profiles compared to garlic extract. The combination of red dragon and garlic extract was more effective to reduce the number of foam cells compared to the extract of red dragon fruit and garlic extract alone.